E-book de intervenções pedagógicas com aplicação das Tecnologias Digitais de Informação e Comunicação (TDICS) para o ensino de sociologia - Arrais, Harrysson Augusto Primo (2024)
This work aims to contribute to the training of teachers, enabling them to use Digital Information and Communication Technologies (DITs) in the teaching-learning process. The choice of the topic arose from the perception of teachers' unpreparedness for the use of TDICs from during the period of the Covid-19 pandemic. The study was carried out in the Professional Master's Program in Sociology on a National Network (PROFSOCIO/UFC) and used theoretical references such as Moran (2012, 2020), Costa et al. (2012) and Chaves (1998), among other authors. Moran explores the personalization and flexibility of the teachinglearning process with TDICs, with an emphasis on the hybrid modality, and encourages student autonomy; Costa et al. discusses the challenges of integrating scientific knowledge, pedagogical methodologies and technical skills in teacher training; Chaves analyzes distance learning, highlighting the need for planning for the effectiveness of technologies. Furthermore, quantitative-qualitative research was carried out with 172 teachers from Ceará, addressing their experiences with TDICs before, during and after the pandemic, and analysis of forums of the course "Training Itinerary - Digital Skills for Teaching", promoted by the Ceará Department of Education, which provided data on digital pedagogical practices in the pandemic context. The results of teaching practices presented in academic works were also examined, such as the experience of the Sociology teacher at School Doutor João Ribeiro Ramos, located in Sobral, and master's theses presented at PROFSOCIO. After collecting and investigating such data, it was found that the definition of pedagogical practices in the context of cyberculture, as well as the distinction between devices, digital interfaces and the different teaching-learning modalities need to be better understood by teachers. Furthermore, the urgency of revisiting the concepts of curriculum and assessment is highlighted, redefining strategies through the exploitation of TDICs. Finally, the "E-book on Pedagogical Interventions with the Application of Digital Information and Communication Technologies (TDICs) for the Teaching of Sociology" was developed, which offers active and collaborative learning strategies, aligned with the guidelines of the National Common Curricular Base (BNCC) and contemporary demands, aiming to promote a more dynamic and integrated education, with conscious and effective use of technologies.